Penerapan Model Kooperatif Tipe Jigsaw terhadap Hasil Belajar Siswa pada Materi Perpindahan Kalor di Kelas V SD Karya Budi Banda Aceh - Crystin Aysera Manullang; Aida Fitri; Suci Fitriani; Rizki Kurniawati (Universitas Syiah Kuala, 2023)
The study is titled Application of Collaborative Puzzle Learning Model to Learning Outcomes of Heat Transfer Materials for Students of Class V SD Karya Budi Banda Aceh. The problem in this study is that teachers often use lectures in teaching, which makes students in a passive state in learning activities. The problem formulation was how to apply the jigsaw cooperative learning model to the learning outcomes of fifth grade students in SD Karya Budi Banda Aceh in heat transfer materials. The purpose of this study was to describe the learning outcomes of fifth grade students in SD Karya Budi Banda Aceh about heat transfer materials using the jigsaw puzzle model. The subjects of this study are the students of Class V, with a total of 28 students. This research method is qualitative while the research type is descriptive. Data collection techniques are performed through testing. Data analysis uses percentage formulas. After analyzing the data, the result obtained is 89.00%. According to the results of the study, it was concluded that the application of the jigsaw cooperative model to heat transfer material could achieve complete student learning outcomes.Keywords: Jigsaw Type Cooperative Model, Learning Outcomes, Heat Transfer Materials, Science